Penguatan Pemahaman Implemantasi Kurikulum Merdeka Bagi Komite Pembelajaran - fernandez, aloysius joakim (Bakti Cendana, 2024)
The headmaster is the most important element in the implementation of the Kurikulum Merdeka. The headmaster is the most important element in the development of an Kurikulum Merdeka in each of the schools. The role of the headmaster is important, so the headmaster needs to continue to be given reinforcement for the implementation of an Kurikulum Merdeka. In order to realize the objectives of this activity, Penguatan Komite Pembelajaran (PKP) activity was carried out. This activity is carried out online with a facilitator. PKP activities involved headmasters, teachers and school supervisors, but in this class only three headmasters attended. This activity was carried out for eighteen days. The activity begins with a presentation of material by the facilitator and continues with the assignment by the participants. The results obtained are that there is an increased understanding of the role of the headmasters in the development of an Kurikulum Merdeka.